Evaluation Of Phytochemical Constituents Of The Roots Of Licorice, Indian Ginseng, Indian Madder And Indian Sarsaparilla - S.REKHA; A. PARVATHI (International Journal of Pharma and Bio Sciences, 2012)
Ethanolic extracts of the dried roots of Glycyrrhiza glabra L. (Licorice),Withania somnifera (L.) Dunal (Indian Ginseng) , Rubia cordifolia L. ( Indian Madder) and Hemidesmus indicus (L.) R.Br. (Indian sarsaparilla) were analysed for their phytochemical constituents. The qualitative analysis showed the presence of various phytochemicals like alkaloids, cardiac glycosides, flavonoids, HCN, indoles, juglones, phenols, saponins, steroids, tannins and terpenoids. Further, Some of these phytochemicals were also quantitatively estimated. The paper deals with the significance of these roots in traditional medical systems with respect to their phytochemicals.